Review. Mostly medieval: In memory of Jacek Fisiak. By Hans Sauer & Piotr P. Chruszczewski (eds.). Academic Publishing, 2020. Pp. xii + 555. - Ogura, Michiko (Studia Anglica Posnaniensia, 2021)
Review. Mostly medieval: In memory of Jacek Fisiak. By Hans Sauer & Piotr P. Chruszczewski (eds.). Academic Publishing, 2020. Pp. xii + 555.